History in Documents: VOC Records from Batavia (17-18th centuries) - Irina Katkova (Manuskripta, 2023)
The present article deals with Malay letters and documents from the archives of the Dutch East India Company (Verenigde Oost-Indische Compagnie – VOC), dating to the seventeenth and eighteenth centuries. The documents belong to the collection of the Russian scholar and collectioner N.P. Likhachev (1862-1936) and have been kept in the Institute of Oriental Manuscripts in St. Petersburg since 1938. The collection of VOC diplomatic letters that was in a possession of to Governor-General Johan van Hoorn (1653-1711), travelled from old Batavia, to Amsterdam and then to St. Petersburg. Fifty-six letters were written in different languages: Malay in Arabic and Javanese scripts, Dutch, Persian, Arabic, Spanish and Chinese. Mostly addressed to Johan van Hoorn the Dutch Governor-General in 1704-1709, they are not only exemplary of the fine art of Malay letter-writing, but also original diplomatic documents and historical sources on Dutch early colonial policy in Malay Archipelago.